On Preventing the Extinction of the Physician-Scientist in Pediatric Pulmonology - Rubenstein, Ronald C.; Kreindler, James L. (Frontiers in Pediatrics, 2014)
While the founders of Pediatric Pulmonology recognized the necessity of research as a vital part of the developing sub-specialty, the field has struggled to develop and maintain physician-scientists and investigators. The clinical growth in Pediatric Pulmonology has resulted in significant challenges in career development faced by physician-scientists who aim to establish or maintain independent investigative programs. Such challenges may only be overcome with changes in how both trainees and established physician-scientists in Pediatric Pulmonology are supported.